ANALISIS PROSES PEMBELAJARAN RAMAH ANAK SELAMA PEMBELAJARAN ONLINE DI KOTA BEKASI - Suharjuddin, Suharjuddin; Yulianti, Yulianti; Saripah, Wa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
The process of learning during Covid-19 pandemic requires the transformation of learning method into line teaching. The objectives of the research are describe and analyze whether the online learning during pandemic Covid-19 in Bekasi City was friendly child conducted or not and to figure out problems faced by students during online learning. Focus of this research is analysis the process of friendly child learning. The problems statement: (1) how is the process of learning to read poetry in class IV during online learning in Bekasi City, (2) What are the problems in reading poetry faced by students during online learning. This is a descriptive qualitative research. The process of data collection was conducted for one full semester. Observation, interview and documentation were instrument of the research. Data is consist of primer and secondary data. Technique of data collection uses observation, interview and documentation. Triangulation of data is essential part in this research. Technique of data analysis uses interactive model (Data collection, data display, data reduction and conclusion drawing). The results show that the process of learning Bahasa Indonesia particularly in learning reading poetry was not fully conducted based on friendly child concept. Problems faced by students, they are: technical problem with online learning, lack of technical skill in speaking, low self-confidence and problem in articulation and poetry appreciation. In order to solve those problems, learning improvement are needed. Covid-19 is one of challenge both for teacher and students to carry out more interactive teaching and learning.